2007
DOI: 10.1007/s10620-006-9245-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral Specific Desensitization in Food-Allergic Children

Abstract: The possibility of obtaining oral desensitization in patients with food allergy is still a matter of debate. We decided to evaluate the safety and efficacy of standardized protocols for oral desensitization with the most common food allergens. Forty-two children (ages up to 16 years) diagnosed as affected by food allergy (on the basis of clinical history, skin prick tests, measurement of specific IgE, and double-blind, placebo-controlled food challenge) underwent a sublingual-oral desensitizing treatment accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 21 publications
4
119
0
4
Order By: Relevance
“…Desensitization refers to a temporary clinical state in which allergen exposure fails to cause allergic symptoms, whereas tolerance indicates clinical nonreactivity to allergen exposure even after long periods of abstinence. Five studies gave oral immunotherapy [34][35][36]38,39 and 2 studies gave subcutaneous immunotherapy. 37,40 Immunotherapy was somewhat effective for desensitization but tolerance and safety were inadequately evaluated.…”
Section: Management Of Food Allergiesmentioning
confidence: 99%
“…Desensitization refers to a temporary clinical state in which allergen exposure fails to cause allergic symptoms, whereas tolerance indicates clinical nonreactivity to allergen exposure even after long periods of abstinence. Five studies gave oral immunotherapy [34][35][36]38,39 and 2 studies gave subcutaneous immunotherapy. 37,40 Immunotherapy was somewhat effective for desensitization but tolerance and safety were inadequately evaluated.…”
Section: Management Of Food Allergiesmentioning
confidence: 99%
“…The optimal dose and length of therapy is also unclear. Previous studies on OIT have used a variety of doses [6,13,16,25] and protocols are heterogeneous, making comparisons among them difficult. In 2012, Keet et al [11] demonstrated that sublingual immunotherapy (SLIT) followed by OIT was much more effective for desensitization than SLIT alone.…”
Section: Clinical Trials Of Oitmentioning
confidence: 99%
“…However, SLIT is not currently recommended for treatment of food allergy [34]. Only few studies have been done in peanut, nuts, kiwi, peach and cow´s milk allergy [35][36][37][38][39], and they showed lower frequencies of adverse reactions compared with OIT, which is likely due to lower doses of allergen administration and the capacity of the mouth mucosa to induce intestinal tolerance. However, the efficacy of SLIT is still debated and characterization of regulatory cells and mechanisms at the buccal mucosa are emerging [40].…”
Section: Sublingual Immunotherapymentioning
confidence: 99%